Consumer Confidence, Islamic Msme Financing, Inflation, Ramadan, And Real Sales: ARDL - Hary Yuda Prasetia; A. Rasikhu Z. Haramain (Student Scientific Creativity Journal, 2026)
This study aims to analyze the influence of the Consumer Confidence Index, Islamic MSME financing, inflation, and Ramadan on the Real Sales Index in Indonesia. The study uses monthly data from January 2022 to June 2025 obtained from Bank Indonesia, the Central Statistics Agency, and Islamic Banking Statistics published by the Financial Services Authority. The analysis method used is Autoregressive Distributed Lag (ARDL) because the results of the Augmented Dickey-Fuller stationarity test indicate a combination of integration orders I(0) and I(1), with no variables integrated at order I(2). Based on the criteria for selecting the best model, the ARDL(3,2,1,2,3) model was obtained. The results of the bounds test indicate a long-term relationship between variables with an F-statistic value of 4.592, which is greater than the upper bound value at the 5 percent significance level. In the long term, the Consumer Confidence Index, Islamic MSME financing, and inflation have a negative and significant effect on the Real Sales Index. Meanwhile, the Ramadan variable is proven to have a positive and significant effect on increasing real sales. The results of this study indicate that consumer psychological factors, monetary conditions, and religious momentum play a significant role in shaping the dynamics of public consumption in Indonesia. Furthermore, diagnostic tests demonstrate that the research model is free from autocorrelation and heteroscedasticity and exhibits a good level of stability, making it suitable for use as a basis for economic analysis and policy formulation.